1984
DOI: 10.1111/j.1365-2230.1984.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of cell proliferation kinetics in the small intestinal epithelium of psoriasis patients

Abstract: Summary Small intestinal biopsies from psoriasis patients and from normal controls were obtained with a multipurpose suction tube. The tissue was incubated with tritiated thymidine and processed for autoradiography. Labelling indices (LI) were calculated by counting labelled cells in all crypt cross‐sections through the entire proliferative compartment. LI was increased in psoriatics as compared to controls indicating alterations in small intestinal epithelial cell kinetics in psoriasis. A continuous labelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…We have demonstrated alterations in enterocyte kinetics without changes in the villus pattern in patients with psoriasis, a disease in which a slight non-specific malabsorption is often found. We suggested that immaturity of the enterocyte might contribute to the impaired absorption (7). In the present study, we demonstrate that PSS patients with x-ray-proven duodenal involvement and diarrhoea have a significantly increased LI as compared to PSS patients without gastro-intestinal disease and normal controls.…”
Section: Discussionsupporting
confidence: 57%
“…We have demonstrated alterations in enterocyte kinetics without changes in the villus pattern in patients with psoriasis, a disease in which a slight non-specific malabsorption is often found. We suggested that immaturity of the enterocyte might contribute to the impaired absorption (7). In the present study, we demonstrate that PSS patients with x-ray-proven duodenal involvement and diarrhoea have a significantly increased LI as compared to PSS patients without gastro-intestinal disease and normal controls.…”
Section: Discussionsupporting
confidence: 57%
“…However, it is interesting that small intestinal epithelial cell proliferation in psoriatic patients has been demonstrated to be increased when compared to control subjects [17]. In addition, psoriatic involvement of mucous membranes may give rise to glossitis, stomatitis, laryngitis, conjunctivitis, and vulvitis [4,5,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the mucosa of the biliary tract may also occur. In psoriatic enteropathy there is an immaturity of the enterocytes due to enhanced epithelial cell tumover ( 12). Whether discrete damage to the biliary epithelium leads to increased cell turnover and a transient cholestasis rcmains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%